Pengaruh Keberadaan Pasar Sungai Lulut Terhadap Kinerja Jalan Martapura Lama KM. 05 - Hawinuti, Riska (P3M Politeknik Negeri Banjarmasin, 2018)
Jalan Martapura Lama is an alternative road connecting Banjarmasin, Martapura and Banjarbaru city and it is under the administration of Banjar Regency. The existence of Sungai Lulut Market in Kilometer 05 consistently causing congestion to the area, especially during peak hours. The purpose of this study is to determine the impact of market activities on the performance of Jalan Martapura Lama KM 05 indicated by the degree of saturation (DS) and the value of the level of road service. The method of primary data collection was by conducting traffic surveys and measuring geometric conditions in the site manually on Tuesday to Thursday, 06-08 February 2018 during the morning rush hour (07.00-08.00 a.m), the noon hour (12.00-14.00 p.m) and afternoon rush hour (16.00 to 18.00 p.m) while the secondary data was obtained from the internet. The calculation refers to Indonesian Highway Capacity Manual (MKJI) 1997. From the calculation results it can be concluded that the impact of market activities on the performance of Jalan Martapura Lama KM 05 indicated by the degree of saturation (DS) and the value of road level of service with the optimum DS is 0,68 with the value of level of road service is C on Thursday’s afternoon rush hour and the minimum DS is 1.34 with the value of level of road service is F on Wednesday’s morning rush hour. With a total frequency of occurrences and side friction class of 571 frequencies, the maksimum friction is incoming and outgoing vehicles on area alongside roads (EEVs) of 446 occurrences on Tuesday in the morning rush hour.